ANALISIS MINAT BELAJAR MATEMATIKA MTs PONPES DAAR – AL ILMI - Caesarani, Sarah; Islamiyah, Izzatul (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
The aim of this research was to analyze the learning interest of junior high school students in learning mathematics. In this study, a qualitative research was used with a descriptive method whose population was students at MTs Daar Al-Ilmi. The sample used was 46 female students. The non-test instrument or questionnaire used in this study, with a total of 20 statement items which includes positive and negative statements. This instrument was created based on 4 indicators of students' interest in learning mathematics. The data analysis technique used in this research is to use the formula for the percentage of student answers which is then described using the criteria for interpreting the results of student answers. The results obtained from analyzing this study indicate that students' interest in learning is an indicator of feeling happy in participating in learning mathematics, having an interest in participating in each learning of mathematics, and having a disciplined attitude in learning mathematics which shows that most students have an interest in learning mathematics